2018
DOI: 10.1016/j.rmed.2018.03.005
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic and airway oxidative stress in competitive swimmers

Abstract: High intensity training in healthy, non-asthmatic competitive swimmers results in marked oxidative stress at the airway and systemic levels, but does not lead to airway inflammation. However, we could not confirm that oxidative stress is associated with bronchial hyperresponsiveness (AHR), which is often observed during the peak exercise training period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…The products of purine nucleotides degradation were two times higher, and the increase in the content of the nitrate anion was 2.5 times higher [15]. Other studies during the training period with reports of systemic oxidative stress and induction of muscle damage markers show that high intensity training in healthy non-asthmatic competitive swimmers resulted in marked oxidative stress at the airway and systemic levels, with the hypothesis that oxidative stress may be associated with bronchial hyperresponsiveness, which is often observed during the peak exercise training period [16]. ROS production by contracting muscle during exercise happens through several mechanisms including activation of endothelial xanthine oxidase, electron leakage at the mitochondrial electron transport chain, inflammatory response, increased release, and auto-oxidation of catecholamines.…”
Section: Exercise-induced Oxidative Stress and Inflammation: The Pmentioning
confidence: 99%
“…The products of purine nucleotides degradation were two times higher, and the increase in the content of the nitrate anion was 2.5 times higher [15]. Other studies during the training period with reports of systemic oxidative stress and induction of muscle damage markers show that high intensity training in healthy non-asthmatic competitive swimmers resulted in marked oxidative stress at the airway and systemic levels, with the hypothesis that oxidative stress may be associated with bronchial hyperresponsiveness, which is often observed during the peak exercise training period [16]. ROS production by contracting muscle during exercise happens through several mechanisms including activation of endothelial xanthine oxidase, electron leakage at the mitochondrial electron transport chain, inflammatory response, increased release, and auto-oxidation of catecholamines.…”
Section: Exercise-induced Oxidative Stress and Inflammation: The Pmentioning
confidence: 99%
“…Repeated exposures to the swimming pool environment during training may partially explain this finding due to chlorine and its by-products, which may irritate the airways by oxidative stress. Skrgat et al 34 have also shown the occurrence of oxidative stress in swimmers during high-intensity training period. Another study reported an enhanced migration of blood eosinophils to airway tissues during strenuous endurance exercise, leading to an increased degranulation of eosinophils and the release of ECP in healthy mountaineers 35 .…”
Section: Discussionmentioning
confidence: 94%
“…A single bout of aerobic and anaerobic exercise has been shown to induce acute increases in systemic biomarkers of oxidative stress (Bloomer and Goldfarb 2004 ). Oxidative stress has been detected in competitive swimmers exposed to a chlorinated environment and has also been implicated in the pathogenesis of asthma (Skrgat et al 2018 ), making it a possible pathway behind the high prevalence of asthma observed in cross-country skiers (Mäki-Heikkilä et al 2020 ). However, we could not detect acute increases in the oxidative stress marker 8-isoprostane concentrations in plasma or urine after exercise in the cold.…”
Section: Discussionmentioning
confidence: 99%